The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1753-6405.12713
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence of admission to permanent residential aged care for Australian women – A competing risk analysis

Abstract: Objective: To provide a direct estimate of the risk of admission to permanent residential aged care among older women while accounting for death, according to housing type and other variables. Methods:A competing risk analysis from 8,867 Australian women born 1921-26, using linked data from the Australian Longitudinal Study on Women's Health (ALSWH), Residential Aged Care (RAC), and the Australian National Death Index. Results:After accounting for deaths, around 35% of women will be admitted to RAC between age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…These findings are consistent with several previous studies that report that older age, higher limitations in ADL, and falls are significantly associated with increased risk of RAC admission [12,31]. An earlier study on this cohort that focused on housing also reported a similar association of housing type with time to first RAC admission [11]. Although, those who are widowed or have multiple conditions are found to have an increased risk of transitioning to RAC in other studies, in our study these participants might be having enough HACC services or alternative services (e.g., HCP which was not covered in our study) to manage their conditions or other care needs in community settings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with several previous studies that report that older age, higher limitations in ADL, and falls are significantly associated with increased risk of RAC admission [12,31]. An earlier study on this cohort that focused on housing also reported a similar association of housing type with time to first RAC admission [11]. Although, those who are widowed or have multiple conditions are found to have an increased risk of transitioning to RAC in other studies, in our study these participants might be having enough HACC services or alternative services (e.g., HCP which was not covered in our study) to manage their conditions or other care needs in community settings.…”
Section: Discussionsupporting
confidence: 92%
“…Although this study provides significant insights into service outcomes of HCP, the participants were from only one HCP provider in New South Wales and Canberra, and were studied for a relatively small observation period. Furthermore, previous separate studies on HACC and RAC have reported that living in remote/rural areas is associated with increased odds of HACC use [7] but decreased risk of entering RAC [11]. Research is yet to explore whether high usage of HACC services reduce the risk of entering RAC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…English speaking, females, 80–89 years old constituted a large segment of our cohort and has been consistent over the years evaluated. Borotkanics et al [21], and Forder et al have reported that females aged between 70 and 90 years are more likely to enter PRAC [22]. Increased longevity is due to better health and primary health care, and so it is not surprising that aged care services are being used more often by people who have lived to a very advanced age which was identified in the study.…”
Section: Discussionmentioning
confidence: 81%
“…Participants with higher baseline age had an increased risk of transitioning from the non-user state to either HACC, RAC, death or transitioning from HACC to RAC. Those who lived in remote/inner/regional areas were associated with an increased hazard of transitioning from the non-user state to HACC [43] but a decreased hazard of transitioning from the non-user state to RAC [44]. These findings may reflect the availability of HACC in those areas, compared with limited accessibility to RAC.…”
Section: Discussionmentioning
confidence: 99%